IN VITRO PROPAGATION OF ANGIOPTERIS EVECTA USING SPORES - POONAM BHATIA; DAMIEN CUPITT; NANJAPPA ASHWATH (BIOTROPIA, 2001)
Techniques of establishing Angiopleris evecta plants  in vitro were studied. Soaking of A. evecta spores in water for 24 hours markedly reduced spore contamination. Soaking of the spores in 1 -2 % of sodium hypochlorite for  less  than 5 minutes allowed satisfactory disinfestation without affecting spore viability. Lower concentration of minerals (1/4 MS), presence of charcoal in the medium and exposure of the spores to light were crucial for spore germination and gainetophytc development of A. evecta. Keywords:   Angiopleris evecta I King fern / spore / MS medium / bleach / light / tissue culture / sporophyte / gamctophytc